PENGARUH MEKANISME TATA KELOLA PERUSAHAAN, RISIKO KEUANGAN, DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA - Sasmito Widi Nugroho (RELASI : JURNAL EKONOMI, 2017)
This study aims to analyze the influence of corporate governance mechanisms, financial risk, and ownership structure on earnings management. Proxy for good corporate governance mechanism is   Managerial ownership, institutional ownership, independent commissioner and independent audit committee. Proksi  for the financial risk is leverage ratio, free cash flow, and the current ratio. Earnings management is measured by discretionary accruals using the model of Kang Sivaramakrishnan. The   sample  of   this   research   is   27   companies   in   the manufacturing  sector  which  were  listed  in  Indonesian  Stock  Exchange  in 2010-2012. The results shows that institutional ownership, independent commissioner, independent audit committee have no effect on earnings management. Managerial ownership and leverage ratio has a positive effect on earnings management. Free cash flow, current ratio and ownership structure has a negative effect on earnings management.